An Overview of the Law of Attorney Fees in the United States: The American Rule is not so Simple After All - Heller, Thomas Allan (Collected Papers of Thomas A. Heller, 2025)
It often is said that in the United States each party pays their own attorney’s fees, win or lose, absent a contractual provision to the contrary or some recognized ground in equity. This basic proposition, which is true as far as it goes, is based on the so-called American Rule, which provides that in the United States each side in a litigated case is responsible for paying their own attorney, regardless of the outcome of the case. On its face this proposition seems simple. On the contrary, however, the laws in the United States governing attorney’s fees are surprising quite complex. This article provides a general survey of the patchwork of laws, federal and to a lesser extent state, and the author will demonstrate that rules and laws governing attorney’s fees are often grounded in important public policy and fundamentally shape important issues, such as access to the courts and the legal system more generally. Unfortunately, many United States citizens have been priced out of the legal market under the current system.